Enhanced IP spoofing defense through clustered interdomain packet filtering strategy - Lee, Soon (2011)
In current Internet communication world, validity of the source of Internet Protocol packet is an important issue. The problems of IP spoofing alarm legitimate users of the Internet. Various spoofing defenses techniques and mechanisms are proposed by researchers, among which, Interdomain Packet Filter (IDPF) architecture proposed by Duan, et al. is promising. Based on the information from Border Gateway Protocol (BGP), IDPF is constructed. Filtering nodes are chosen based on vertex cover of the graph. This thesis presents a clustered strategy for selection of filtering nodes for IDPF architecture. Clusters of filtering nodes are chosen from the Autonomous System with highest number degree. Through analysis and simulation, the effectiveness of IDPF with Clustered Filtering was measured. The work presented here has profound implications for future studies of IP spoofing defense under IDPF.